Therapeutic Relationship and Dropout in High-Risk Adolescents’ Intensive Group Psychotherapeutic Programme - Hauber, Kirsten; Boon, Albert; Vermeiren, Robert (Frontiers in Psychology, 2020)
Objective Dropout rates are a prominent problem in youth psychotherapy. An important determinant of dropouts is the quality of the therapeutic relationship. This study aimed to evaluate the association between the therapeutic relationship and dropouts in an intensive mentalization-based treatment (MBT) for adolescents with personality disorders. Methods Patients (N = 105) included were either dropouts (N = 36) or completers (N = 69) of an intensive MBT. The therapeutic relationship was measured with the child version of the Session Rating Scale (C-SRS), which was completed by the patient after each group therapy session. For each patient, the treatment termination status (dropout or completer) was indicated by the treatment staff. The reliable change index (RCI) was calculated for the C-SRS to determine significant changes in the therapeutic relationship. Results While both groups started with similar scores on the C-SRS, the scores between dropouts and completers differed significantly at the end of the treatment period. On average, during therapy, an increase was seen in the scores of completers, and a decrease was seen in the scores of dropouts. While dropouts could not be predicted based on the C-SRS scores, a significant decrease (RCI) in C-SRS scores during the last two sessions occurred more often for dropouts than for completers. Conclusion Our findings show that to prevent dropouts, the patient’s judgment of the quality of the therapeutic relationship should be monitored continuously, and decreases discussed with the patient and the group.